High-performance supercapacitor based on three-dimensional MoS2/graphene aerogel composites. (16th December 2015) - Yang, MinHo; Jeong, Jae-Min; Huh, Yun Suk; Choi, Bong Gill
Abstract: Three-dimensional (3D) MoS2 /chemically modified graphene (CMG) aerogel composites are prepared by a hydrothermal reduction reaction. Such 3D architecture enables effective electron and ion transfer and stable distribution of 2D nanosheets. 3D MoS2 /CMG composites are investigated as supercapacitor electrode materials, showing a high specific capacitance of 268 F g −1 at 0.5 A g −1, a high rate capability with 87.7% retention up to 15 A g −1, and a good cycle life with 93% retention for 1000 cycles. Electrochemical impedance spectroscopy analysis reveals that the 3D interconnected structure of MoS2 /CMG enhances the charge transfer and facilitates diffusion of electrolyte ions.